A bibliometric analysis of digital storytelling in language education - Ayşegül Avcı; Yusuf Kasımi (Literacy Trek, 2023)
This study provides a comprehensive overview of the research in digital storytelling and identifies the key themes and trends in this area. Digital storytelling is an emerging field that has gained significant attention in recent years. In this study, we conducted a bibliometric analysis of the digital storytelling literature to examine this field's growth and development. The data collected from the Web of Science database was analyzed quantitatively, revealing a significant growth in digital storytelling as a field in recent years. The analysis revealed that the number of publications in this area has noticeably increased. The field's most productive authors, journals, and institutions were identified, and the key themes, trends, and challenges in digital storytelling research were identified. The analysis revealed that the most frequent keywords in the literature were "technology," "literacy," "education," language," "students," "learning-motivation," "pedagogy," "English," and "stories." The key themes that emerged from the literature were the use of digital storytelling in education, the role of technology in digital storytelling, and the use of digital storytelling for social change. The co-occurrence of keywords revealed strong connections between the themes of education, learning, and technology in digital storytelling research. The analysis also revealed that the field of digital storytelling had grown rapidly in recent years, with a significant increase in the number of publications. The number of publications in digital storytelling has increased exponentially in the last decade, and this trend is expected to continue. The analysis also revealed that the majority of publications in digital storytelling are in the subfields of education and English. The analysis revealed that the field of digital storytelling is still in its early stages, and there is a need for more research in this area.